2018
DOI: 10.1063/1.5019209
|View full text |Cite
|
Sign up to set email alerts
|

Computational analysis for selectivity of histone deacetylase inhibitor by replica-exchange umbrella sampling molecular dynamics simulations

Abstract: We performed protein-ligand docking simulations with a ligand T247, which has been reported as a selective inhibitor of a histone deacetylase HDAC3, by the replica-exchange umbrella sampling method in order to estimate the free energy profiles along ligand docking pathways of HDAC3-T247 and HDAC2-T247 systems. The simulation results showed that the docked state of the HDAC3-T247 system is more stable than that of the HDAC2-T247 system although the amino-acid sequences and structures of HDAC3 and HDAC2 are very… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…In a previous study, the REUS simulations were applied to elucidate the selectivity of a ligand between HDAC2 and HDAC3. 11 In the present simulations, the obtained PMFs have shown the tendency which is consistent with the kinetic selectivity and we examined the difference in details of the structures between HDAC1 and HDAC2. We have found that the differences of binding properties between the two enzymes are mainly due to an un-conserved residue, suggesting that the un-conserved residue provides HDAC2 with a tight fitting of the inhibitor and causes HDAC1 a misfit of the inhibitor.…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…In a previous study, the REUS simulations were applied to elucidate the selectivity of a ligand between HDAC2 and HDAC3. 11 In the present simulations, the obtained PMFs have shown the tendency which is consistent with the kinetic selectivity and we examined the difference in details of the structures between HDAC1 and HDAC2. We have found that the differences of binding properties between the two enzymes are mainly due to an un-conserved residue, suggesting that the un-conserved residue provides HDAC2 with a tight fitting of the inhibitor and causes HDAC1 a misfit of the inhibitor.…”
Section: Introductionsupporting
confidence: 58%
“…By taking the reaction coordinate for the umbrella potential as the distance between a ligand and a docking site of a protein, REUS was applied to the docking problem of a ligand to a protein. [9][10][11] This method has been extended to two-dimensional replica-exchange methods to enhance the sampling further. [12][13][14] The results of REUS simulations give a potential of mean force (PMF) which characterizes binding properties and structures which show the snapshots along the binding process.…”
Section: Introductionmentioning
confidence: 99%
“…In this way, the position-dependent PMF as well as the position-dependent diffusion constant plays a central role, and we need to obtain these quantities accurately and efficiently from molecular dynamics (MD) simulations. With respect to the PMF (which is also referred to as the free energy landscape and free energy along a reaction coordinate, among other terms), many approaches have been developed and applied to various systems. In this study, we focus on the methodology to obtain the position-dependent diffusion constant.…”
Section: Introductionmentioning
confidence: 99%
“…Since each KDAC isozyme is thought to have specific substrate proteins/lysine residues and to be associated with distinct diseases, isozymeselective KDAC inhibitors are of interest as chemical tools and therapeutic agents with few side effects. 93) In our group, we have reported several isoform-selective inhibitors against HDAC3, 40,94) HDAC6, 95,96) HDAC8, 36,41) and SIRT2 39,[97][98][99] by SBDD, LBDD, strategic chemistry approaches, and their combination. In this section, I present the studies on SIRT2selective inhibitors identified by combining SBDD with drug design based on an enzymatic mechanism.…”
Section: Lysine Acetylation Modulators and Their Applicationmentioning
confidence: 99%